Virtual reality simulation in robot-assisted surgery: meta-analysis of skill transfer and predictability of skill. Issue 2 (17th April 2021) - Schmidt, M W; Köppinger, K F; Fan, C; Kowalewski, K -F; Schmidt, L P; Vey, J; Proctor, T; Probst, P; Bintintan, V V; Müller-Stich, B -P; Nickel, F
Abstract: Background: The value of virtual reality (VR) simulators for robot-assisted surgery (RAS) for skill assessment and training of surgeons has not been established. This systematic review and meta-analysis aimed to identify evidence on transferability of surgical skills acquired on robotic VR simulators to the operating room and the predictive value of robotic VR simulator performance for intraoperative performance. Methods: MEDLINE, Cochrane Central Register of Controlled Trials, and Web of Science were searched systematically. Risk of bias was assessed using the Medical Education Research Study Quality Instrument and the Newcastle–Ottawa Scale for Education. Correlation coefficients were chosen as effect measure and pooled using the inverse-variance weighting approach. A random-effects model was applied to estimate the summary effect. Results: A total of 14 131 potential articles were identified; there were eight studies eligible for qualitative and three for quantitative analysis. Three of four studies demonstrated transfer of surgical skills from robotic VR simulators to the operating room measured by time and technical surgical performance. Two of three studies found significant positive correlations between robotic VR simulator performance and intraoperative technical surgical performance; quantitative analysis revealed a positive combined correlation ( r  = 0.67, 95 per cent c.i. 0.22 to 0.88). Conclusion: Technical surgical skills acquired through robotic VR simulator training can be transferred to the operating room, and operating room performance seems to be predictable by robotic VR simulator performance. VR training can therefore be justified before operating on patients. Graphical Abstract: Abstract : This systematic review and meta-analysis presents current evidence on transferability of surgical skills acquired on robotic VR simulators to the real operating room, and on the predictability of intraoperative performance by robotic VR simulator performances. The limited data currently available support the use of robotic VR simulators for surgical skill acquisition and assessment.